Adopsi Nilai Budaya Osing dalam Kerangka Objektivitas Meaning of Life - Husni Hanafi; Nur Hidayah; Andi Mappiare AT (Graduate School of Universitas Negeri Malang, 2018)
Abstract: Meaning of life is the value of life that is necessary to possess and fulfill by person in every part of his life. Meaning of life has three sources of value namely the value of Creative, Experential, and Attitudional which also influenced by the objective component of intersubjectivity of the culture. Osing as one of the cultures in Indonesia has an objective concept in the meaning of life of Osing society. The adoption of the meaning of life of Osing culture was done through content analysis on the interview result to the leader of Osing in Kemiren Village, Banyuwangi. The meaning of life Osing culture has twelve values compiled in accordance with the three sources of meaning of life value.Abstrak: Meaning of life merupakan nilai kehidupan yang perlu untuk dimiliki dan dipenuhi setiap individu dalam setiap bagian kehidupannya. Meaning of life memiliki tiga sumber nilai yakni nilai Creative, Experential, dan Attitudional yang turut dipengaruhi oleh komponen objektif dari intersubjektivitas budaya individu. Osing sebagai salah satu budaya di Indonesia memiliki konsep objektif dalam meaning of life masyarakat Osing. Pengkajian atas adopsi meaning of life budaya Osing dilakukan melalui analisis isi terhadap hasil wawancara kepada ketua Adat Osing di Desa Kemiren, Banyuwangi. Meaning of life budaya Osing memiliki duabelas nilai yang disusun sesuai dengan tiga sumber nilai meaning of life.